The Influence of Mangarock Online Comics in Teaching Writing a Narrative Text - Hadi, Muhamad Sofian; Izzah, Lidiyatul; Larasati, Ineke (JOLLT Journal of Languages and Language Teaching, 2021)
Manggarock online comics are used by many researchers in enhancing studentsâ€™ language skills. This study aims to investigate the effectiveness of Manngarock online comics to improve students’ writing skills at the ninth-grade students of SMP Harapan Masa, Depok, Indonesia. This study is categorized as a quantitative study using Pre-experimental design. To attain the data, researchers employ writing tests. The sample of this study is all students of the ninth-grade students of SMP Harapan Masa. The students are subjected to Manggarock online comics. To know the efficacy of Manggarock online comics, researchers apply statistical analysis, which is t-test. The studentsâ€™ writing skills in the pre-tests and the post-test are calculated using descriptive statistical analysis. Based on the results of analysis, the mean score of students is 79.26. meanwhile, the value of t-test (16.243) was higher than t-table (2.015) in a significant level of 5% (0.05). Therefore, the alternative hypothesis (Ha) proposed was accepted while the null hypothesis was rejected. From the results of this analysis, this study can be concluded that the Manggarock online comics have a positive effect on students’ writing skills at the ninth-grade students.